PENERAPAN TEKNIK REFRAMING ORANG TUA DALAM MENINGKATKAN MOTIVASI ANAK KETIKA GAGAL MENGGAPAI KAMPUS IMPIAN: Bimbingan dan Konseling Pendidikan Islam - Nurhayati Kusuma Dewi; Nurul khoerunisa; Said.; Imalatul Khairat (STKIP Subang, 2025)
The failure of a child to gain admission to their dream university often leads to significant psychological impacts, such as a decline in motivation, self-confidence, and enthusiasm for learning. In such situations, the role of parents becomes crucial in providing appropriate emotional support. One approach that can be utilized is reframing, a technique in communication and psychology aimed at shifting an individual’s perspective on an event to a more constructive and positive one. This study aims to describe how the application of reframing techniques by parents can enhance a child’s motivation after failing to enter their desired university. The research employs a qualitative approach using case studies of several families whose children did not gain admission to their target universities. The findings indicate that parental reframing—such as transforming the narrative of failure into an opportunity for growth, offering alternative and realistic perspectives, and emphasizing effort over outcomes—can help children overcome disappointment and regain motivation to pursue other academic goals. Therefore, reframing techniques have proven to be effective as a communication strategy that supports children’s mental resilience in facing failure.